Стимулювання розвитку смарт-промисловості в просторовому аспекті: досвід для України - Залознова, Ю.С.; Чекіна, В.Д. (Економіка промисловості, 2025)
У статті розглянуто стан цифрової трансформації промисловості В країнах ЄС на сучасному етапі розвитку. Встановлено причини зниження темпів «смартизації» промислових підприємств. Виявлено чинники, що вплинули на створення програм і проєктів стимулювання розвитку смарт-промисловості в різному просторовому середовищі (міжнаціональні, національні, регіональні, місцеві). Виконано аналіз деяких спеціальних програм розвитку країн Європи, а також проєктів і програм транснаціонального співробітництва, спрямованих на впровадження стратегій стимулювання розвитку смарт-промисловості. Розроблено пропозиції щодо вдосконалення процесів «смартизації» вітчизняної промисловості. The paper examines the state of industrial digital transformation in EU countries at the current stage of development. The role of industry and the level of industrialization in European countries are determined. The reasons for the slowdown in the pace of smartification of industrial enterprises are identified, including COVID-19 pandemic, slow growth in R&D spending, insufficient level of employees` digital awareness and digital skills. The factors that attracted the attention of experts and prompted the creation of programs and projects to stimulate the development of smart industry in different spatial environments (international, national, regional, local) are identified: difficulties of integrating new Industry 4.0 business models into the activities of SMEs, lack of capital investments in smart tools and infrastructure, problems related to IT security, etc. The directions in which the new technical and economic paradigm of Digitizing European Industry will be implemented are given: creation of an intelligent production system, creation of a virtual copy of the production environment, decentralization of cyber-physical systems, real-time management, orientation towards IT services, flexibility of systems. The experience of European countries is considered from the standpoint of their contribution to the development of smart industry and an analysis of some special development programs based on high-tech clusters, new mechanisms of interaction between local authorities, business and scientific and educational institutions is conducted. Transnational cooperation projects and programs aimed at implementing strategies to stimulate the development of smart industry in various areas are analyzed: intellectual specialization, participation of SMEs in European research and innovation programs, strengthening the circular economy, the implementation of Industry 5.0 in European high-tech industries. The problems faced by industrialists when making decisions on the digitalization of production processes and administration of economic activity are identified. Proposals have been developed to improve the processes of domestic industry smartification. Examples of EU projects and initiatives to support Ukrainian researchers and career opportunities for manufacturers of innovative products have been provided, the advantages of cooperation with European partners and some difficulties that need to be eliminated to create new markets and opportunities for the country, regions and companies have been identified.